Predestination: Uncanny (mis)recognition, science fiction and 'home movie' moments. Issue 2 (1st August 2019) - Baker, Djoymi
This article uses the science fiction film Predestination (Spierig Brothers, 2014) to examine the combined role of sound and image in the subjective 'home movie moment'. Vivian Sobchack argues that even within a fiction film, an audience member might recognize a familiar location, momentarily pulling them out of a fictional engagement with the screen text and instead facilitating an engagement more aligned with that of a home movie. Given Sobchack's interest in phenomenology, it is noticeable that she focuses exclusively on the cinematic image in this particular work. I argue that liminal blurring can occur between modes of engagement, triggered by both image and sound. In Predestination, the puzzle narrative that colludes with the uncanny voice is paralleled by the way that the sights and sounds of Melbourne facilitate uncanny home movie moments, shot through with science fictional estrangement.